Improvement of thermal properties of polybenzoxazines synthesized from an oligonuclear phenolic compound without sacrificing toughness by introducing crosslinkable groups separated by rigid biphenyl linkers. (16th January 2023) - Shibatsuka, Taichi; Kawauchi, Takehiro
Abstract: Novel allyl-, ethynyl-, and furfuryl-containing polyfunctional benzoxazine monomers were synthesized, and the mechanical and thermal properties of their thermosets were investigated. The benzoxazines OP-ala, OP-ea, and OP-fu were successfully synthesized with high yield from an oligonuclear phenolic compound with a 4, 4ʹ-dimethylenebiphenyl group as the phenol linker; paraformaldehyde; and the corresponding amines, allylamine, m -ethynylanilline, and furfurylamine, respectively, using a microwave heating technique. Despite the introduction of the crosslinkable groups, the brown polybenzoxazine films obtained via thermal curing up to 240 °C showed sufficient toughness, as shown through tensile testing. Dynamic mechanical analysis revealed that the glass transition temperature ( T g ) of the thermosets considerably increase due to the introduction of the crosslinkable groups; POP-ala, POP-ea, and POP-fu films showed T g values of 289 °C, 272 °C, and 269 °C, respectively. Moreover, thermogravimetric analysis showed that the thermal stability also increased, and the 5% weight-loss temperature of POP-ea was >430 °C. Graphical abstract: Image 1 Highlights: Allyl-, ethynyl-, and furfuryl-containing polyfunctional benzoxazines were synthesized from an oligonuclear phenolic compound. Despite the introduction of the crosslinkable groups, the cured products exhibited sufficient toughness. The cured products showed high glass transition temperature ( T g : 237–262 °C) and degradation temperature ( T d5 : 360–431 °C).